2015
DOI: 10.3390/nu7125517
|View full text |Cite
|
Sign up to set email alerts
|

Greater Calcium Intake is Associated with Better Bone Health Measured by Quantitative Ultrasound of the Phalanges in Pediatric Patients Treated with Anticonvulsant Drugs

Abstract: We aimed to investigate and compare the effects of chronic antiepileptic therapy on bone health in pediatric patients using quantitative ultrasound of the phalanges (QUS) and controlling for potential confounding factors, particularly nutrient intake. The amplitude-dependent speed of sound (Ad-SoS) was measured in 33 epileptic children and 32 healthy children aged 6.5 ± 3.1 and 6.3 ± 1.1 (mean ± SD) years, respectively. There were no significant differences in the demographics such as age, weight and height be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…We found that for both the vertebrae and femur, the BMD of the valproic acid group was significantly lower than that in the healthy control group, which implies that long-term use of valproic acid decreased the BMD of children with epilepsy. Testing the BMD could help find changes in bone structure in the early stages in children with epilepsy who taken valproic acid, thus providing the clue for early treatment [31]. Long-term use of AEDs may decrease the level of vitamin D, thus reduce the BMD and affect bone structure.…”
Section: --mentioning
confidence: 99%
“…We found that for both the vertebrae and femur, the BMD of the valproic acid group was significantly lower than that in the healthy control group, which implies that long-term use of valproic acid decreased the BMD of children with epilepsy. Testing the BMD could help find changes in bone structure in the early stages in children with epilepsy who taken valproic acid, thus providing the clue for early treatment [31]. Long-term use of AEDs may decrease the level of vitamin D, thus reduce the BMD and affect bone structure.…”
Section: --mentioning
confidence: 99%
“…A small Italian study (n=164, aged 2-21 years) investigating how anticonvulsants affect DXA and QUS measures in girls with or without Rett Syndrome found that anticonvulsant therapy was associated with lower bone measures, although fracture risk was not elevated [18]. Similarly, a crosssectional study conducted in Spain found that valproate, but not carbamazepine, phenobarbital, lamotrigine, topiramate, vigabatrine or phenytoin was associated with lower QUS measures in children (n=65, aged 6.5±3.1 years) compared to non-users; despite having 27.3% of their treated group taking two or more anticonvulsants [19]. On the other hand, several studies have looked at associations between anticonvulsant use and BMD [29][30][31][32], although most studies have been conducted in patients with epilepsy and in paediatric populations [33].…”
Section: Discussionmentioning
confidence: 92%
“…Anticonvulsants have been associated with increased fracture risk in adults [10,16] and decreased BMD in children [17]. Few studies have investigated anticonvulsant use on QUS parameters [18,19]. A preclinical analysis of levetiracetam use in rats decreased bone quality, but not BMD, suggesting that DXA measurements may not su ciently detect all anticonvulsant-related bone de cits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a crosssectional study conducted in Spain found that valproate, but not carbamazepine, phenobarbital, lamotrigine, topiramate, vigabatrine or phenytoin was associated with lower QUS measures in children (n = 65, aged 6.5 ± 3.1 years) compared to non-users? ; despite having 27.3% of their treated group taking two or more anticonvulsants [20]. On the other hand, several studies have looked at associations between anticonvulsant use and BMD [31][32][33], with most studies conducted primarily in patients with epilepsy and in paediatric populations [15].…”
Section: Discussionmentioning
confidence: 99%
“…Anticonvulsants have been associated with increased fracture risk in adults [15,18] and decreased BMD in children [19]. Few studies have investigated anticonvulsant use on QUS parameters [20][21][22][23]. A preclinical analysis of levetiracetam use in rats decreased bone quality, but not BMD, suggesting that DXA measurements may not su ciently detect all anticonvulsant-related bone de cits [24].…”
Section: Introductionmentioning
confidence: 99%